(untitled) (Jurnal Teknologi (Sciences & Engineering), 2025)
The MIG welding process is widely used in industry because it is cost-effective, can be done with all positions, and has high productivity. The accuracy of the welding process and the relative welding parameters influence the welding quality. A CNC welding system can be used in welding to produce precise and stable welds. The experimental welding process in this study used materials ASTM A36, the welding process on a CNC MIG machine with current and travel speed parameters. The experimental results of the welding process identify defects with the Non-Destructive Test (NDT)-Liquid Penetrant Test (LPT)/Dye-Penetrant Test and Destructive Test (DT) including Tensile Test, Hardness Vickers, Macrostructure, and Microstructure, aimed at determining defects that occur. The results of the NDT and DT tests showed that there were porosity defects on the surface, slag, and incomplete penetration in the internal area of the metal weld. The welding results are best visually with a dye penetrant test at a current of 70 A a travel speed of 100 mm/min, and 80 A travel speed of 150mm/min and 200 mm/min. The hardness test results show that there is an influence on the welding current and travel speed. The tensile test results of welding results show the influence of current and travel speed, where the highest tensile strength at a current of 90A is 278 MPa, and the tensile strength at a travel speed of 200 mm/minute has a tensile strength of 286 MPa.